Development of an Ecology STEM-Based Assessment Tool for Scientific Creativity in Junior High School Science Education - Iwan Wicaksono; Normala Ismail; Inggrid Syaharani Pribadi (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The level of scientific creativity among Indonesian junior high school students remains relatively low, partly due to the limited scope of school based assessment instruments that fail to comprehensively measure this competency, particularly in the context of environmental sustainability and STEM integration. This study aims to develop an eco-STEM based scientific creativity assessment instrument on the topics of temperature, heat, and expansion for seventh grade junior high school students, as well as to determine its quality in terms of validity, reliability, discriminative power, difficulty level, and practicality. This study employed a modified Borg and Gall model consisting of nine stages. The research subjects included expert validators, science teachers, observers, and seventh grade students at SMP Negeri 12 Jember. Data were collected through validation sheets, a practicality questionnaire, and a test instrument comprising 28 open-ended items. Data analysis included content validity (Aiken’s V), item validity (Pearson correlation), reliability (Cronbach’s alpha), discriminant validity, difficulty level, and practicality percentage. The results showed that the instrument met validity criteria with a percentage of 76–79%. All 28 items were declared valid with calculated r values (0.703–0.945) > table r. The instrument’s reliability was very high with a Cronbach’s alpha of 0.990. The discriminative power falls into the adequate category (0.255–0.389). The distribution of difficulty levels is close to ideal (25% easy, 36% moderate, 39% difficult). The practicality score is 86.7% (highly practical). This assessment instrument is suitable for science teachers to use in evaluating students’ scientific creativity in a comprehensive and contextual manner